Shared decision‐making related to treatment of haemophilia: A scoping review of influential factors and available support tools - Sun, Haowei (Linda); Klaassen, Robert J.; Anger, Dana L.; Mendell, Ari L.; Olatunde, Shade (Haemophilia : the official journal of the World Federation of Hemophilia, 2024)
Introduction Treatment selection in haemophilia is increasingly challenging given evolving therapeutic options and the need for individualization. Shared decision‐making (SDM) approaches have recently gained interest, though a synthesis of available studies is lacking. Aim A scoping review was conducted to summarize literature reporting on factors impacting treatment SDM in haemophilia and tools or models available to support such decisions. Methods PubMed, Embase, the Cochrane Library, Web of Science and grey literature were searched for studies published through August 2023. Original studies reporting on facilitators and barriers to haemophilia SDM and SDM tools were included and analyzed for themes, characteristics and gaps. Results A total of 625 records were identified and 14 unique studies were selected (factors influencing treatment SDM, n = 7; SDM tools, n = 7). The studies typically included input from persons with haemophilia, caregivers and healthcare practitioners (HCPs). Thematic organization of factors influencing SDM revealed three main categories: knowledge, patient characteristics and HCP‐patient interactions. Availability of information was a commonly reported facilitator of SDM, while poor HCP‐patient engagement was a commonly reported barrier. Tools varied in focus, with some facilitating general treatment SDM while others supported selection of certain therapy types. The studies underscored additional factors critical for SDM, such as alignment of HCP‐patient perceptions, shared language and tailoring of tools to specific subpopulations. Conclusion Few studies report on treatment SDM factors and tools in haemophilia; available tools vary considerably. It remains unclear whether published tools have been successfully implemented into clinical practice. Additional research is warranted.